PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, KESEJAHTERAAN KERJA, DAN KEDISIPLINAN KERJA TERHADAP KINERJA GURU SMP NEGERI DI KECAMATAN KEPIL KABUPATEN WONOSOBO TAHUN PELAJARAN 2013/2014 (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The Impact of Principal Leadership, Welfare Work and Work Discipline Toward Teacher Performance of Junior High School in Kepil Subdistricts of Wonosobo regency in Academic year 2013/2014This study 1) aims to determine the impact of school leadership, welfare received by the teacher, and discipline of work on teacher performance of Junior High School in District Kepil of Wonosobo Regency.2) to prove which variable has the most dominant an teacher’s perfomence.The population of this research are all the govern teachers in Kepil subdistrict of Junior High Sshool concict of 94 teachers, all of them are as the sample. The trials conducted during the research are used for the valid data wich serve as the data reaserch as well. Data were collected using questionnaires which were answered immediately by the teachers. The data gathered from the questionnaires were analyzed statistically by multiple regression techniques.Described by percentage, the results showed that the majority of respondents stated that the principal leadership variables,welfare received by teachers variable, and the discipline variables were categorized very high, whereas the teachers’s performance variables is also categorized very high. As conclusion, the independent variable of school leadership, teacher welfare and work discipline together have positive and significant impact on the performance of teachers. The partial analysis shows that of school leadership has significantly positive impact on teacher’s performance. Teacher welfare is also has significantly positive impact on teacher’s performance, discipline variable has significantly positive impact on teacher performance. This suggests that if the leadership of the principal, welfare received by teachers, and discipline of work increase; the performance of teachers will also increase.